Dashboard Design to Monitor the Number of Students of the Faculty of Information Technology, Tarumanagara University - Tony, Tony; Handhayani, Teny; Dayanti, Afina Putri (STMIK Widya Cipta Dharma, 2024)
Students in a study program within the faculty are important stakeholders in higher education. The continuity and efficiency of teaching and learning activities depend significantly on the number of students in a study program. The Faculty of Information Technology at Tarumanagara University currently offers two study programs: Informatics Engineering and Information Systems. While Tarumanagara University already has a system for managing student data, it requires further development to remain competitive with other universities, particularly those offering information technology programs. The existing system provides only basic information, such as whether the number of students this year has increased or decreased compared to the previous year. However, it lacks the ability to deliver a comprehensive overview of student data. To address this limitation, a monitoring system is needed to provide more accurate and systematic information. This system will be visualized in the form of a dashboard, offering insights into trends such as the number of students, their school origins, gender distribution, and address/region of origin. The dashboard design is based on the waterfall model of the software development life cycle (SDLC) and is developed using Power BI Desktop.